First, rewrite this expression as:
#(16/8)(x/x^2)(y^3/y) => 2(x/x^2)(y^3/y)#
Next, we can use these rules of exponents to simplify the #x# term:
#a = a^color(red)(1)# and #x^color(red)(a)/x^color(blue)(b) = 1/x^(color(blue)(b)-color(red)(a))# and #a^color(red)(1) = a#
#2(x/x^2)(y^3/y) => 2(x^color(red)(1)/x^color(blue)(2))(y^3/y) => 2(1/x^(color(blue)(2)-color(red)(1)))(y^3/y) =>#
#2(1/x^color(red)(1))(y^3/y) => 2(1/x)(y^3/y) => 2/x(y^3/y)#
We can now use these rules of exponents to simplify the #y# term:
#a = a^color(red)(1)# and #x^color(red)(a)/x^color(blue)(b) = x^(color(red)(a)-color(blue)(b))#
#2/x(y^3/y) => 2/x(y^color(red)(3)/y^color(blue)(1)) => 2/x(y^(color(red)(3)-color(blue)(1))) => 2/x(y^2) => (2y^2)/x#